Water productivity improvement of cereals and foods legumes in the Atbara Basin of Eritrea - Grando, Stefania; Ghebretatios, I.; Amlesom, S.; Ceccarelli, Salvatore; Maatougui, M.H. el; Niane, A.A.; Mustafa, Y.; Sarker, A.; Abdalla, O.; Berhane, T.; Abraha, N.; Tsegay, S.; et al. (CGIAR Challenge Program on Water and Food, 2010)
The project ‘Water Productivity Improvement of Cereals and Food Legumes in the Atbara Basin of Eritrea’ is an example of organization and implementation of farmers’ participatory research, conducted utilizing the available indigenous knowledge while empowering farming communities. Farmers have been partners in technology development with extension and research, with full decision-making power in planning, implementation, monitoring, and evaluation.